Characterisation of the tensile properties of Demineralised Cortical Bone when used as an anterior cruciate ligament allograft. (October 2020) - Hexter, Adam T.; Shahbazi, Shirin; Thangarajah, Tanujan; Kalaskar, Deepak; Haddad, Fares S.; Blunn, Gordon
Abstract: Background: Graft choice in anterior cruciate ligament (ACL) reconstruction remains controversial and some grafts fail due to inadequate osteointegration. Demineralised cortical bone (DCB) is an osteoinductive collagen-based scaffold. The aim of this study was to measure the tensile properties of DCB from different locations and from different ages, and determine its compatibility with current ACL fixation systems. Methods: The tensile properties of DCB manufactured from femur and tibia of young (9 month) and old (2–3 years) sheep was measured to determine the most appropriate graft choice. The ultimate load and stiffness of DCB allograft using two fixation systems, interference screws and sutures tied around screw posts, was measured ex vivo in an ovine ACL reconstruction model. Comparison was made with superficial digital flexor tendon (SDFT) and ovine ACL. Results: DCB derived from young tibia had the highest ultimate load and stiffness of 67.7 ± 10.6 N and 130.2 ± 64.3 N/mm respectively. No DCB fixation system reached the published peak in vivo force through the ovine ACL of 150 N. SDFT fixation with interference screws (308.2 ± 87.3 N) did reach the in vivo threshold but was significantly weaker than ovine ACL (871.0 ± 64.2 N). Conclusion: The tensile properties of DCB were influenced by the donor age and bone. Owing to inferior tensile properties and incompatibility with suspensory fixation devices, this study indicates DCB is inferior to current tendon grafts options for ACL reconstruction. Highlights: The source of Demineralised Cortical Bone (DCB) influences its ultimate tensile stress and stiffness. DCB derived from tibia has a greater ultimate tensile stress than femur. DCB lacks the structural integrity to withstand interference screws. DCB lacks the flexibility required for use with suspensory femoral fixation. DCB is mechanically inferior to current tendon grafts for ACL reconstruction.